Bilateral Candida keratitis in an HIV patient with asymptomatic genitourinary candidiasis in Uganda - Arunga, Simon; Kwaga, Teddy; Leck, Astrid; Hu, Victor H.; Burton, Matthew J. (Medical Mycology Case Reports, 2018)
A 35-year-old male presented with Candida keratitis in the left eye. He was HIV positive with a CD4 of 352 cells/ μL. The eye quickly deteriorated, despite intensive antifungal treatment and was eviscerated. Five months later, he re-presented with Candida keratitis in his right eye. A focal source of Candida infection was suspected and a urine culture identified Candida spp, despite being asymptomatic for genitourinary candidiasis. He was subsequentlytreated with good outcome (max. 75 words)
Keywords: Fungal keratitis; Candida keratitis; Genitourinary candidiasis; HIV; Uganda